The work engagement and organizational silence among nurses: the mediating role of coworker support - Shen, Ying; Chen, Xiaodan; Zhang, Heran; Lv, Xiangyan (Frontiers in Public Health, 2025)
IntroductionOrganizational silence is prevalent in healthcare and negatively affects nurses and organizational development. This study determined whether coworker support mediates the relationship between organizational silence and work engagement among nurses.MethodsA quantitative cross-sectional survey was conducted using convenience sampling. The Utrecht Work Engagement Scale-17, Peer Supporting Scale, and Employee Silence Behavior Survey Questionnaire were used to measure the key variables. Descriptive statistics, Pearson correlation analysis, and a structural equation modeling with bootstrap method were performed.ResultsA total of 597 registered nurses from 21 general hospitals in China participated. Nurses’ work engagement (72.09 ± 20.33), coworker support (108.60 ± 20.66), and organizational silence (32.23 ± 11.06) were at moderate levels. Work engagement was positively correlated with coworker support, while both work engagement and coworker support were negatively correlated with organizational silence (all p < 0.01). Mediation analysis indicated that the direct effect value of work engagement on organizational silence was −0.155 (95% CI: −0.217 ~ −0.094, p < 0.001). The indirect effect value of work engagement on organizational silence through coworker support was −0.197 (95% CI: −0.236 ~ −0.160, p < 0.001), accounting for 56.13% of the total effect (−0.351; 95%CI: −0.410 ~ −0.292, p < 0.001).ConclusionWork engagement was negatively correlated with organizational silence, in which coworker support played a partial mediating role. It is recommended to enhance the positive impact of work engagement on organizational behavior through strengthening coworker support among nurses, thereby reducing organizational silence, fostering a better work environment, and ultimately enhancing the quality of nursing care.